Theoretical Analysis of a Solar PV-Wind Hybrid Power System for Energy Generation in Kutch Region. (August 2019) - Desai, A; Ray, A; Mukhopadhyay, I
Abstract: Solar PV-Wind Hybrid Power System that uses renewable sources to supply power to grid to meet the power requirement. Theoretical Mathematical Modeling and its Generation analysis showed that solar radiation and wind are the most important physical variables for the Solar PV-Wind power system design. The study proposes Solar PV-Wind based system, affordable by local government standards to respond to the electricity demand of that state, is the one with an irradiance between 2.6 to 7 kWh/Day/m 2 and wind speed between 6.6 to 15.5 miles per hour. The annual average daily yield, annual average monthly yield and total average Capacity Utilization Factor (CUF) are 5 kWh/kWp/Day, 157 kWh/kWp/Month and 21 % Respectively for solar pv-wind hybrid power system total Generation for Kutch region. The model shows that with the help of Solar PV-Wind Hybrid Power System we can forecast the energy generation of minimum 30 % and maximum 70 % energy generation which can be utilize in state with the modification of existing infrastructure hence infrastructure cost can be saved and waste land between the wind mills can also be utilized.